Islamic mission and inter-religious dialogue in a minority context: the Jama'at-i-Islami of India - Sikand, Yoginder (Islam and Christian-Muslim relations, 2002)
This article seeks to examine how the Jama 'at-i-Islami Hind (JIH), the Indian unit of the Jama'at, has sought to come to terms with a situation of considerable religious pluralism, despite its firm belief in Islam as the only true and perfect religion and its commitment to a vision of Islam as an all-embracing socio-political system. In particular, it focuses on the JIH's own missionary agenda and examines how attempts have been made to mould it in order to take into account the imperative of building bridges with people of other faiths, by critically examining some of the writings of key JIH ideologues as well as recent initiatives made by the JIH to promote inter-faith dialogue in India.